Misi Emansipatoris Alqur’an dalam Relasi Seksualitas Antara Majikan dan Budak Perempuan - Rosmini, Rosmini (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2015)
The Qur'an was revealed during the oppression of man by man more institutionalized in the form of slavery. This institution fostered and developed by international public civilization in a variety of ways in which the war became a major facility in the preservation of slavery in addition to other facilities. Among of the them are human trafficking because of poverty, slave inheritance itself and by other means inhumane. In this context, the Qur’an’s transformative declaration in restoring human status of slaves should be appreciated including the concept of Qur'an in managing sexuality relations between male employer and female slaves. Emancipatory movement of the Qur'an in this case implementated by positioning the women slave as part of a marginal women community who able to accompany the life of a man in a "married" or "marry her" with the believer independent men (mukmin).